Kandungan Komponen Serat Tepung Rebung Bambu Tabah (Gigantochloa nigrociliata buse-kurz) - Dylla Hanggaeni Dyah Puspaningrum (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2015)
Tabah bamboo shoots (Gigantochloa nigrociliata BUSE-KURZ) is one of the varieties local bamboo shoots usually consume and having many the womb nutrients. Research aims to understand fiber components that is added to tabah bamboo shoots flour. Testing the fiber component of bamboo shoots done by processing the tabah bamboo shoots into flour and is expected to be used with easy to apply as a substitute ingredient in other food products. Fiber analysis covering components analysis cellulose, hemicellulose and lignin in tabah bamboo shoots in each different parts (apical , middle and basal) that has been processed into flour using Chesson method. The design of experiment that is used a single-factor randomized block design (RBD) The research results show that component fibers in tabah bamboo shoots flour is highest on the part the basal of the namely 30,99% (bk) hemisellulose , 37,55% (bk) cellulose and of the womb lignin not markedly dissimilar in the middle of 3,85 % (bk) and that part the basal of the 4,05% (bk).